Analyzing multimedia tools and language teaching - Kumar, Tribhuwan; Malabar, Sayama; Benyo, Ahmed; Amal, Bakhrul Khair (Linguistics and Culture Review, 2021)
This study analyzes the use of multimedia tools to teach English in non-English speaking nations and highlights the issues that teachers and English students confront. A better instrument for the exploration of a novel teaching approach has been the increasingly growing scientific tools and techniques such as multimedia technology. Multimedia technology, in particular, in non-native language contexts, plays an essential role in English language education. It also intends to raise awareness of the strategies to effectively deploy non-mutual English speakers as language teachers. The study presents a detailed analysis of the role of multimedia tools and technology. Advantages and disadvantages of multimedia tools and technology are described at length, recommendations are made and conclusion is drawn. It is believed that the use of multimedia technology can ensure effective language teaching and enhance learners’ linguistic abilities.